Neurobiology of migraine progression - Wanakorn Rattanawong; Alan M. Rapoport; Anan Srikiatkhachorn (Neurobiology of Pain, 2022)
Chronic migraine is one of the most devastating headache disorders. The estimated prevalence is 1.4–2.2% in the population. The factors which may predispose to the process of migraine progression include high frequency of migraine attacks, medication overuse, comorbid pain syndromes, and obesity. Several studies showed that chronic migraine results in the substantial anatomical and physiological changes in the brain. Despite no clear explanation regarding the pathophysiologic process leading to the progression, certain features such as increased sensory sensitivity, cutaneous allodynia, impaired habituation, identify the neuronal hyperexcitability as the plausible mechanism. In this review, we describe two main mechanisms which can lead to this hyperexcitability. The first is persistent sensitization caused by repetitive and prolonged trigeminal nociceptive activation. This process results in changes in several brain networks related to both pain and non-pain behaviours. The second mechanism is the decrease in endogenous brainstem inhibitory control, hence increasing the excitability of neurons in the trigeminal noceptive system and cerebral cortex. The combination of increased pain matrix connectivity, including hypothalamic hyperactivity and a weak serotonergic system, may contribute to migraine chronification.
Keywords: Migraine and Headache Studies; Trigeminal Neuralgia and Treatments; Vestibular and auditory disorders